2016
DOI: 10.1002/maco.201508763
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion protection of thickness reduced plasma electrolytic layers on AZ31

Abstract: In the present study plasma electrolytic oxidation of magnesium in fluoride free alkaline solution were used to form thin oxide layers with high corrosion protection. The relation between potassium hydroxide and sodium silicate was varied in the electrolyte. The plasma electrolytic process was performed as current controlled unipolar pulse technique. The microstructure of the formed layers were investigated by X-ray diffraction and scanning electron microscopy. The electrochemical behavior was studied by linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Sirivasan et al concluded that thin but compact coatings formed on magnesium at low current densities during the PEO process offer a better corrosion protection. This conclusion is confirmed by Schneider et al, which have recently studied the electrochemical behavior of plasma electrolytically formed oxide layers on AZ31 with a thickness of d ≈ 2 μm. The corrosion current densities in aerated 0.01 M NaCl solution amount to j corr ≈ 0.03 up to 0.1 μA/cm 2 and the passive current densities to j p ≈ 0.08 and 1.1 μA/cm 2 .…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…Sirivasan et al concluded that thin but compact coatings formed on magnesium at low current densities during the PEO process offer a better corrosion protection. This conclusion is confirmed by Schneider et al, which have recently studied the electrochemical behavior of plasma electrolytically formed oxide layers on AZ31 with a thickness of d ≈ 2 μm. The corrosion current densities in aerated 0.01 M NaCl solution amount to j corr ≈ 0.03 up to 0.1 μA/cm 2 and the passive current densities to j p ≈ 0.08 and 1.1 μA/cm 2 .…”
Section: Introductionsupporting
confidence: 66%
“…Figure shows the open circuit potential in aerated 0.01 M NaCl over 180 min. The open circuit potential of the PEO anodized samples is only slightly more positive than the ocp measured on bare AZ31 under the same conditions (−1.6 V SCE ) and the difference between the layers formed in a bath with and without suspension of inhibitor‐loaded zeolites is marginal. More interesting is the comparison of the linear sweep voltammograms as shown in Figure .…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Therefore, Mg–H 2 O 2 semi‐fuel cells have been applied as attractive submarine power sources . However, because pure Mg as the anode material naturally causes self‐discharge reactions and lag effects, it has the following disadvantages: (1) low‐current efficiency, (2) weak‐corrosion resistance, and (3) long‐occurrence time . Considering that the corrosion process is controlled by the pitting corrosion rate, these problems can be solved by doping other elements (such as zinc, aluminum, and manganese) into the magnesium alloys …”
Section: Introductionmentioning
confidence: 99%